(untitled) (Academic Journal of Internal Affairs, 2021)
Lone offences are becoming more common across Europe among people with an immigrant background. In Hungary, the number of crimes related to migration and people with an immigrant background is small. The appearance of migration in the media, on the other hand, generates serious emotions. It can create groupings and trigger emotions in individuals to commit acts of wrongdoing. The phenomenon of migration has both positive and negative effects. One of the most frightening of the negative effects is the way it reshapes our thinking. This can be observed in the relationship between people with an immigrant background and the inhabitants of the host country. In my study I examine a lone perpetrator who emerges as a result of migration, focusing on the issue of prevention. I show how criminal policy and prevention models work, or do not work. At the end of the study, I outline a possible prevention model.